Impact of Ecological Policy on Environmental Sustainability - Savlabek Kistaubaev (Zien Journals, 2022)
That article focuses on the need to ensure environmental sustainability in the world and the importance of policy in this regard
Keywords: Ecological policy; ecological attitude; global problams; geological powers